Synergising rural change based on modern rural approach: Formulation of a modern Malaysian rural development framework / Mohd Fadzil Abdul Rashid ... [et al.] - Abdul Rashid, Mohd Fadzil; Rashid, Kushairi; Muhamad, Ana Kashfi; Ahmad, Aizazi Lutfi; Azman, Muhammad Azrul Azwan (2021)
The Malaysian government aims to transform rural areas into economic focal points, improve rural livelihoods, living environment and narrow the life quality gaps between those living in urban and rural areas. This aspiration can be seen through a translation in many national development policies, particularly in Dasar Perancangan Fizikal Desa Negara (the DPF Desa Negara 2030), Dasar Pembangunan Luar Bandar (the DPLB 2030) and the most current is Wawasan Kemakmuran Bersama (the WKB 2030). Inspired by the government directive-aspirations and the emergence of new technologies in rural practices, nationally and globally, this paper discusses the formulation of a framework for rural development in Malaysia based on the modern rural approach; that is a solution to synergise rural change and social well-being of the community. The process undertakes to formulate the framework comprised into two main stages, namely focused literature study and review of the existing policies and strategies to identify the key assessment elements and criteria for modern rural development, and conduct an expert view survey to validate the developed elements and criteria and then formulate a modern Malaysian rural development framework (FMRD). The FMRD has finally been formulated by incorporating all the important elements and criteria of the DPF Desa Negara 2030 and the DPLB 2030 as well as integrating them with the smart technologies and ICT practices to reflect a holistic approach for rural problems. This paper concludes that the FMRD is a timely approach for the rural assessment to maximise the rural performance towards the future niches in Malaysia - rural sustainability-resilient-and-smart.